2021
DOI: 10.3390/nu13062057
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic Dietary Therapies in Patients with Autism Spectrum Disorder: Facts or Fads? A Scoping Review and a Proposal for a Shared Protocol

Abstract: Autism spectrum disorder (ASD) is a neurodevelopmental disorder with increasing incidence. An expanding body of literature is examining connections between ASD and dietary interventions. Existing reports suggest a beneficial effect of ketogenic dietary therapies (KDTs) in improving behavioral symptoms in ASD. In this context, the purpose of this scoping review was to identify and map available evidence in the literature about the feasibility and potential efficacy of KDTs in pediatric patients with ASD and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 42 publications
(153 reference statements)
0
12
0
Order By: Relevance
“…They found that probiotic supplementation altered the composition of gut microbiota and the level of plasma cytokines were decreased after treatment. Similarly, Varesio et al(2021) reported that ketogenic diet therapy had bene cial effects in improving behavioral symptoms in autism due to changes in gut microbiota. To the best of our knowledge, this is the rst research assessing the therapeutic effects of UDCA in an experimental autism model.…”
Section: Discussionmentioning
confidence: 99%
“…They found that probiotic supplementation altered the composition of gut microbiota and the level of plasma cytokines were decreased after treatment. Similarly, Varesio et al(2021) reported that ketogenic diet therapy had bene cial effects in improving behavioral symptoms in autism due to changes in gut microbiota. To the best of our knowledge, this is the rst research assessing the therapeutic effects of UDCA in an experimental autism model.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers of animal model studies proved that KD might be an effective intervention in alleviating ASD symptoms [52,53]. Furthermore, larger cohort studies found that the use of KD results in noticeable improvements in: learning, social behaviour, speech, cooperation and reduction of hyperactivity in ASD patients [5,40,54].…”
Section: Dietary Models In Asdmentioning
confidence: 99%
“…However, ketogenic dieting should be recommended with caution, as the high-fat percentage (65-90%) can be associated with GID and may lead to nutritional deficiencies, due to low tolerability and the high food selectivity in children with ASD [150]. Gastrointestinal side effects of ketogenic diets in children with ASD included constipation, diarrhea, and vomiting, which occurred within 2-4 weeks of the ketogenic diet onset [169].…”
Section: High-fat Dietsmentioning
confidence: 99%